Identification of long noncoding RNAs (lncRNAs) and co-transcriptional analysis of mRNAs and lncRNAs in transcriptomes of Anopheles gambiae - Xu, Jiannong; Hu, Kai; Riehle, Michelle M.; Khadka, Vedbar S. (Frontiers in RNA Research, 2025)
IntroductionAnopheles gambiae is a primary malaria vector mosquito in Africa. RNA-seq based transcriptome analysis has been widely used to study gene expression underlying mosquito life traits such as development, reproduction, immunity, metabolism, and behavior. While it is widely appreciated that long non-coding RNAs (lncRNAs) are expressed ubiquitously in transcriptomes across metazoans, lncRNAs remain relatively underexplored in An. gambiae, including their identity, expression profiles, and biological functions. The lncRNA genes were poorly annotated in the current reference of the PEST genome of An. gambiae. In this study, a set of publicly available RNA-seq datasets was leveraged to identify lncRNAs across diverse contexts, including whole mosquitoes, mosquito cells and tissues (such as hemocytes, midguts, and salivary glands), as well as under various physiological conditions (e.g., sugar-feeding, blood-feeding, bacterial challenges, and Plasmodium infections).MethodsA Transcript Discovery module implemented in the CLC genomics workbench was used to identify lncRNAs from selected published RNA-seq datasets.ResultsAcross this pool of transcriptomes, 2684 unique lncRNA genes, comprising 4082 transcripts, were identified. Following their identification, these lncRNA genes were integrated into the mosquito transcriptome annotation, which served as a reference for analyzing both mRNAs and lncRNAs for transcriptional dynamics under various conditions. Unsurprisingly, and similar to what has been reported for mRNAs, lncRNAs exhibited context-dependent expression patterns. Co-expression networks constructed using weighted gene co-expression network analysis (WGCNA) highlighted the interconnections among lncRNAs and mRNAs, which provide potential functional networks in which these lncRNAs are involved. Furthermore, we identified polysome-associated lncRNAs within polysome-captured transcripts, suggesting that lncRNAs are likely involved in translation regulation and contribute to coding capacity for micropeptides. The analysis of a ChIP-seq dataset revealed a correlation between transcriptional activities of lncRNAs and observed epigenetic signatures.DiscussionOverall, our study demonstrated that lncRNAs are transcribed alongside mRNAs in various biological contexts. The genome-wide annotation of lncRNA genes and integration into the PEST reference genome enable the simultaneous co-analysis of mRNA and lncRNA, which will enhance our understanding of their functions and shed light on their regulatory roles in An. gambiae biology.